Festschrift in honour of Kathy Charmaz - Bryant, Antony; Clarke, Adele E. (Studies in symbolic interaction, 2022)
Kathy Charmaz (1939-2020) was the developer of Constructivist Grounded Theory (CGT), a key method in qualitative research internationally and across many disciplines and professions. She was Professor Emerita of Sociology at Sonoma State University, California, and former Director of its Faculty Writing Program. Her book, Constructing Grounded Theory, is the definitive guide to developing a constructivist perspective, and is the seminal title for anyone serious about doing CGT research. This Festschrift to honour Kathy Charmaz's scholarship features fourteen chapters plus an editors' introduction, exploring CGT extensively, examining topics including "Indigenization" of the method, its approaches to decolonizing research, uses of CGT in social justice research, and the legacies of Kathy Charmaz's remarkable mentorship. Edited by Antony Bryant and Adele E. Clarke, both of whom co-authored and edited with Kathy, and eminent scholars of qualitative methods in their own right, this is a glowing tribute to her long and distinguished career.